Polyester resin composition, adhesive, and laminate
Patent Information
- Application Number
- JP2023134825
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-22
- Publication Date
- 2025-03-07
AI Technical Summary
【0009】 本発明のポリエステル樹脂組成物によれば、ポリエステルフィルムや金属に対する接着性に優れており、また接着後は、冷熱衝撃試験、湿熱試験を施しても接着力の低下が小さく、耐久性に優れる接着層を形成しうる、接着剤を提供することができる。本発明のポリエステル樹脂組成物を含む接着剤は、耐冷熱性、耐湿熱性の高さから、フレキシブルフラットケーブルに好適に用いられる。
Smart Images

Figure 2025029929000001 
Figure 2025029929000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyester resin composition, an adhesive, and a laminate. [Background technology]
[0002] Flexible flat cables (hereinafter sometimes referred to as FFCs), which consist of rectangular conductors arranged at regular intervals and sandwiched between insulating films, have been widely used for the internal wiring of electronic devices, and efforts are being made to make electrical appliances thinner and lighter.
[0003] Polyester film has traditionally been used as the insulating film that makes up such FFCs because of its balance of mechanical properties, electrical properties, cost, etc., and polyester resin, which has excellent electrical properties and adhesive properties, has been used as the adhesive for bonding this insulating film to conductors such as metals.
[0004] Furthermore, FFCs, which are characterized by being thin, light, and less prone to miswiring, are increasingly being used in the automotive field for various wiring and components, as they enable modularization of parts and expansion of interior space. Accordingly, there is a demand for high-performance and highly reliable FFCs that can be used in harsh in-vehicle environments, and adhesives are also required to have cold and heat resistance and moist heat resistance that can withstand environmental changes between low and high temperatures. In response to these issues, for example, Patent Document 1 uses a crystalline polyester resin and an amorphous polyurethane resin to improve adhesion and heat resistance.
[0005] However, the adhesive layer of Patent Document 1 does not take into consideration resistance to cold and heat at all, and is insufficient in terms of resistance to moist heat. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2008-150443 A Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention aims to solve the above-mentioned problems and to provide a polyester resin composition which has excellent adhesion to polyester films and metals, can be suitably used as an adhesive for FFCs used in internal wiring of electronic devices, and has excellent cold-heat resistance and moist heat resistance. [Means for solving the problem]
[0008] Means of the Invention The present inventors have conducted extensive research to solve the above problems, and as a result have found that a polyester resin and a polyisocyanate having specific structures can solve the above problems, thereby completing the present invention. That is, the gist of the present invention is as follows. (1) A resin composition containing a polyester resin and a polyisocyanate, wherein the polyester resin is composed of a polycarboxylic acid component containing 80 mol % or more of an aromatic carboxylic acid in 100 mol % of an acid component and a glycol component containing 1 mol % or more of a polyalkylene glycol in 100 mol % of a glycol component, and the polyisocyanate is a pentamethylene diisocyanate derivative. (2) The polyester resin composition according to (1), wherein the equivalent ratio (NCO / OH) of the isocyanate group to the hydroxyl group of the polyester resin is 0.5 to 5.0. (3) The polyester resin composition according to (1) or (2), wherein the polyester resin has a number average molecular weight of 10,000 to 35,000. (4) The polyester resin composition according to (1) or (2), wherein the polyalkylene glycol is polytetramethylene ether glycol. (5) An adhesive comprising the polyester resin composition according to (1) or (2). (6) A laminate comprising an adhesive layer made of the adhesive according to (5). (7) A flexible flat cable having the laminate described in (6). Effect of the Invention
[0009] According to the polyester resin composition of the present invention, it is possible to provide an adhesive that has excellent adhesion to polyester films and metals, and after adhesion, shows little decrease in adhesive strength even when subjected to a thermal shock test and a moist heat test, and is capable of forming an adhesive layer with excellent durability. The adhesive containing the polyester resin composition of the present invention is preferably used for flexible flat cables because of its high resistance to thermal shock and moist heat. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention will be described in detail below. The polyester resin composition of the present invention (hereinafter may be simply referred to as "resin composition") contains a polyester resin having a specific structure and a polyisocyanate.
[0011] <Polyester resin> The polyester resin constituting the resin composition of the present invention is a copolymer containing, as constituent components, a polyvalent carboxylic acid component and a glycol component.
[0012] The polyvalent carboxylic acid component constituting the polyester resin must contain 80 mol% or more of aromatic dicarboxylic acid in 100 mol% of the acid component, and more preferably 90 mol% or more. If the content is less than 80 mol%, the cohesive strength and glass transition temperature of the polyester resin will decrease, resulting in poor cold and heat resistance and wet heat resistance. As the aromatic dicarboxylic acid, terephthalic acid is preferred from the viewpoint of adhesion to the substrate and durability, and isophthalic acid is preferred from the viewpoint of solvent solubility, and terephthalic acid and isophthalic acid may be used in combination.
[0013] In the present invention, examples of polyvalent carboxylic acid components that can be used other than terephthalic acid and isophthalic acid include, but are not limited to, phthalic acid, phthalic anhydride, naphthalenedicarboxylic acid, 4,4'-dicarboxybiphenyl, 5-sodium sulfoisophthalic acid, 5-hydroxy-isophthalic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecanedioic acid, hexadecanedioic acid, heptadecanedioic acid, octadecanedioic acid, nonadecanedioic acid, eicosane diacid, docosane diacid, maleic acid, furan diacid ... Examples of the anhydrides include malic acid, itaconic acid, mesaconic acid, citraconic acid, dimer acid, 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 2,5-norbornenedicarboxylic acid and its anhydride, tetrahydrophthalic acid and its anhydride, trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid, trimellitic anhydride, pyromellitic anhydride, benzophenonetetracarboxylic acid anhydride, trimesic acid, ethylene glycol bis(anhydrotrimellitate), glycerol tris(anhydrotrimellitate), and 1,2,3,4-butanetetracarboxylic acid.
[0014] The glycol component constituting the polyester resin must contain 1 mol % or more of polyalkylene glycol in 100 mol % of the glycol component, and more preferably 1 to 20 mol %. If the content is less than 1 mol %, the adhesiveness, cold and heat resistance, and wet heat resistance will be poor. If it exceeds 20 mol %, blocking resistance may be insufficient.
[0015] Examples of polyalkylene glycols include polyethylene glycol, polytetramethylene ether glycol, polypropylene glycol, polyhexylene glycol, polynonanediol, and poly(3-methyl-1,5-pentane)diol. Among these, polytetramethylene ether glycol is preferred from the viewpoint of adhesiveness.
[0016] The number average molecular weight of the polyalkylene glycol is preferably 500 to 3000, and more preferably 500 to 2000. If the number average molecular weight is less than 500, the resulting copolymerized polyester resin may have poor cold / heat resistance and moist heat resistance, whereas if the number average molecular weight exceeds 3000, the adhesiveness may be poor.
[0017] As the glycol component constituting the polyester resin, a glycol component other than polyalkylene glycol can be used, but is not particularly limited thereto. Examples of the glycol component include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, 2,2-butylethylpropanediol, 1,2-propanediol, 2-methyl-1,3propanediol, 3-methyl-1,5pentanediol, 1,4-cyclohexadecanediol, and the like. Examples of bisphenols include bisphenol A (ethylene oxide adducts) such as 2,2-bis[4-(hydroxyethoxy)phenyl]propane, 1,3-cyclohexanedimethanol, 1,2-cyclohexanedimethanol, tricyclodecane dimethanol, spiroglycol, diethylene glycol, triethylene glycol, dipropylene glycol, glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, and bisphenols such as 2,2-bis[4-(hydroxyethoxy)phenyl]propane (ethylene oxide adducts of bisphenol S).
[0018] The polyester resin may be copolymerized with other components other than the polyvalent carboxylic acid component and the glycol component, if necessary, within the range that does not impair the effects of the present invention. The copolymerization ratio of the other components is preferably less than 50 mol % of the polyester resin.
[0019] Other components include, for example, hydroxycarboxylic acids such as lactic acid, oxirane, glycolic acid, 2-hydroxybutyric acid, 3-hydroxybutyric acid, 4-hydroxybutyric acid, 2-hydroxyisobutyric acid, 2-hydroxy-2-methylbutyric acid, 2-hydroxyvaleric acid, 3-hydroxyvaleric acid, 4-hydroxyvaleric acid, 5-hydroxyvaleric acid, 6-hydroxycaproic acid, 10-hydroxystearic acid, and 4-(β-hydroxy)ethoxybenzoic acid; and aliphatic lactones such as β-propiolactone, β-butyrolactone, γ-butyrolactone, δ-valerolactone, and ε-caprolactone.
[0020] The polyester resin may also contain a monocarboxylic acid, a monoalcohol, or the like as a constituent component. Examples of monocarboxylic acids include lauric acid, myristic acid, palmitic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, benzoic acid, p-tert-butylbenzoic acid, cyclohexanoic acid, and 4-hydroxyphenylstearic acid. Examples of monoalcohols include octyl alcohol, decyl alcohol, lauryl alcohol, myristyl alcohol, cetyl alcohol, stearyl alcohol, and 2-phenoxyethanol.
[0021] <Characteristics of polyester resin> The polyester resin in the present invention preferably has a glass transition temperature of 45° C. or less, more preferably 25° C. or less. If the glass transition temperature of the polyester resin exceeds 45° C., the adhesiveness may be poor. The lower limit of the glass transition temperature is not particularly limited, but is preferably −40° C. from the viewpoint of blocking resistance. Methods for controlling the glass transition temperature of the polyester resin include adjusting the content or molecular weight of the aromatic component.
[0022] The number average molecular weight of the polyester resin of the present invention is preferably from 10,000 to 35,000, and more preferably from 10,000 to 30,000. If the number average molecular weight of the polyester resin is less than 10,000, the adhesiveness may be poor, and if it exceeds 35,000, the crosslink density may decrease, resulting in poor cold and heat resistance and poor wet heat resistance. In addition, the melt viscosity and solution viscosity of the resulting polyester resin may increase, resulting in poor handling properties.
[0023] Methods for controlling the molecular weight of polyester resin include a method of terminating polymerization at a predetermined melt viscosity during polycondensation, a method of adding a depolymerization agent after once producing a polyester with a high molecular weight, a method of adding a monofunctional carboxylic acid or a monofunctional alcohol in advance, etc. In the present invention, the molecular weight may be controlled by any of the above methods, but it is preferable that trifunctional or higher components are arranged not only at the terminals of the polyester but also within the molecular chain.
[0024] When an alcohol component is used as the depolymerization agent, a hydroxyl group can be added to the polyester end, and when an acid component is used, an acid value can be added to the polyester end. Examples of such depolymerization agent components include ethylene glycol, butanediol, trimethylolpropane, isophthalic acid, trimellitic anhydride, and pyromellitic acid.
[0025] <Method of producing polyester resin> Next, a method for producing the polyester resin will be described. First, a combination of monomers such as polycarboxylic acid and glycol is appropriately selected and polymerized by a known polymerization method to obtain a polyester resin. That is, the raw material monomers are charged into a reaction vessel, and then an esterification reaction is carried out, followed by polycondensation by a known method until a desired molecular weight is reached, whereby a polyester resin can be produced. The esterification reaction is carried out, for example, at a temperature of 180° C. or higher for 4 hours or longer.
[0026] The polycondensation reaction is generally carried out under reduced pressure of 130 Pa or less, at a temperature of 220 to 280° C., using a polymerization catalyst. The polymerization catalyst is not particularly limited, and examples thereof include titanium compounds such as tetrabutyl titanate, metal acetates such as zinc acetate, magnesium acetate, and zinc acetate, organic tin compounds such as antimony trioxide, hydroxybutyltin oxide, and tin octoate, and organic sulfonic acid compounds such as 2-sulfobenzoic anhydride, o-sulfobenzoic acid, m-sulfobenzoic acid, p-sulfobenzoic acid, 5-sulfosalicylic acid, benzenesulfonic acid, o-aminobenzenesulfonic acid, m-aminobenzenesulfonic acid, p-aminobenzenesulfonic acid, p-toluenesulfonic acid, methyl p-toluenesulfonate, 5-sulfoisophthalic acid, and salts thereof.
[0027] The amount of polymerization catalyst used is 0.1 to 20 × 10 per mole of the acid component, because a small amount will slow down the reaction, and an excessive amount will deteriorate the color tone of the resulting polyester resin. -4 It is preferably molar.
[0028] When depolymerization is carried out, the reaction temperature is preferably 160 to 280° C., more preferably 160 to 220° C., and the reaction time is preferably 0.5 to 5 hours.
[0029] <Polyisocyanate> The resin composition of the present invention must contain a pentamethylene diisocyanate derivative as a polyisocyanate, and other polyisocyanate derivatives (such as aromatic isocyanate derivatives such as tolylene diisocyanate derivatives, alicyclic isocyanate derivatives, and hexamethylene diisocyanate derivatives) result in a poor balance between adhesion and cold and heat resistance / humid heat resistance. In addition, when pentamethylene diisocyanate that has not been modified or added is used, the crosslinking effect is poor and durability is poor, resulting in significant deterioration in both adhesion and cold and heat resistance / humid heat resistance.
[0030] Examples of the pentamethylene diisocyanate derivative include isocyanurate, adduct, biuret, uretdione, allophanate, prepolymer having an isocyanate residue, and complexes thereof, etc. Examples of these polyisocyanates include those commercially available from Mitsui Chemicals under the trade names "STABIO D-370N" and "STABIO D-376N."
[0031] The equivalent ratio (NCO / OH) of the isocyanate group to the hydroxyl group of the polyester resin is preferably 0.5 to 5.0, and more preferably 0.5 to 4.0. If the equivalent ratio is less than 0.5, the cold / heat resistance and moist heat resistance may be poor, and if it exceeds 5.0, the adhesiveness may be poor.
[0032] <Adhesive> The adhesive of the present invention contains the resin composition of the present invention. When preparing the adhesive, it is preferable to dissolve the resin composition of the present invention in an organic solvent. The organic solvent is not particularly limited as long as it dissolves the resin composition of the present invention, and examples thereof include aromatic solvents such as toluene, xylene, solvent naphtha, and solvent, ketone solvents such as methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, alcohol solvents such as methyl alcohol, ethyl alcohol, isopropyl alcohol, and isobutyl alcohol, ether solvents such as diethyl ether, ethyl cellosolve, butyl cellosolve, tetrahydrofuran, and 1,4-dioxane, and ester solvents such as ethyl acetate, normal butyl acetate, cellosolve acetate, and carbitol acetate. These organic solvents may be used alone or in combination of two or more.
[0033] The adhesive of the present invention may contain a flame retardant or a flame retardant assistant, which can impart flame retardancy. Examples of the flame retardant include hexabromocyclododecane, bis(dibromopropyl)tetrabromo-bisphenol A, bis((dibromopropyl)tetrabromo-bisphenol S, tris(dibromopropyl)isocyanurate, tris(tribromoneopentyl)phosphate, decabromodiphenylene oxide, brominated epoxy resin, bis(pentabromophenyl)ethane, tris(tribromophenoxy)triazine, ethylene bis(tetrabromophthalic)imide, ethylene bispentabromophenyl, polybromophenylindane, brominated polystyrene, TBBA polycarbonate, brominated polyphenylene oxide, polypentabromobenzyl acrylate, [2,2-bis(chloromethyl)-1,3-propanediyl]bisoxybis Examples of the flame retardants include halogen-based flame retardants such as tetrakis(2-chloroethyl) phosphonate, tris(1-methyl-2-chloroethyl) phosphate, and 2,2-bis(bromomethyl)-3-chloropropyl phosphate = bis[2-chloro-1-(chloroethyl)ethyl] phosphate; nitrogen-based flame retardants such as aliphatic amine compounds, aromatic amine compounds, triazines, melamines, benzoguanamines, methylguanamines, cyanuric acid, cyan compounds, aliphatic amides, aromatic amides, urea, and thiourea; and phosphorus-based flame retardants such as polyphosphates, phosphinates, phosphate esters, condensed phosphate esters, and phosphazenes. Examples of the flame retardant assistant include antimony trioxide, zinc stannate, and zinc borate. These additives can be used alone or in combination of two or more types.
[0034] The content of the flame retardant in the solid content of the adhesive is preferably 10 to 50 mass %, and more preferably 20 to 40 mass %. If it is less than 10 mass %, the flame retardant effect may be insufficient, and if it exceeds 50 mass %, the adhesiveness may be poor. The content of the flame retardant auxiliary in the polyester resin composition is preferably 10 to 50% by mass, and more preferably 20 to 40% by mass. If it is less than 10% by mass, the flame retardant effect may be insufficient, and if it exceeds 50% by mass, the adhesion may be poor.
[0035] In addition, the adhesive of the present invention may contain a curing agent, an antioxidant, a heat stabilizer, a pigment, and other additives in order to further improve the performance according to the purpose. The curing agent is not particularly limited as long as it is a compound that has reactivity with the functional group of the polyester resin, and examples thereof include epoxy, melamine, and carbodiimide. Examples of the antioxidant include hindered phenol compounds and phosphorus-based antioxidants. Examples of the heat stabilizer include phosphoric acid. Examples of the pigment include titanium oxide, chromium oxide, iron oxide, aluminum oxide, and carbon black.
[0036] Other additives include crystal nucleating agents such as talc and silica, lubricants, fillers, foaming agents, crosslinking agents, plasticizers, hydrolysis inhibitors, dispersion stabilizers, leveling agents, antiblocking agents, and antistatic agents.
[0037] <Laminate> The adhesive of the present invention obtained as described above can be applied to an appropriate substrate (for example, a film or inorganic glass) to form a laminate.
[0038] The laminate of the present invention includes a layer made of the adhesive of the present invention (hereinafter, may be referred to as an adhesive layer). Among them, it is preferable to use a film as the substrate, and it is more preferable to use a laminate in which a film layer / adhesive layer / metal layer are laminated in this order, and it is further preferable to use a laminate in which a film layer / adhesive layer / metal layer / adhesive layer / film layer are laminated in this order.
[0039] The film layer is preferably a polyester film such as polyethylene terephthalate, polybutylene terephthalate, or polyethylene naphthalate, but may also be a film made of a resin such as polyvinyl chloride, polyvinylidene chloride, polycarbonate, polyarylate, polyamide, polyolefin, polyethersulfone, polysulfone, polystyrene, or methacrylic.
[0040] The metal layer is preferably a layer in which a plurality of copper wires are arranged as conductors, but the metal constituting the conductor may be iron, aluminum, tinplate, etc., or these may be plated with tin, zinc, etc., or may be chemically treated with zinc phosphate, chromate, etc.
[0041] A suitable method for producing the laminate of the present invention is to apply an adhesive containing the resin composition of the present invention and, if necessary, various additives to a film layer, dry it, and then bond it to a metal layer by a conventionally known method such as heat sealing, roll bonding, or hot pressing.
[0042] The method for coating the adhesive layer onto the film layer is not particularly limited, and known methods such as reverse roll coating, gravure coating, die coating, comma coating, and spray coating can be used.
[0043] <Application> Adhesives containing the resin composition of the present invention can be used for the purpose of bonding electric / electronic components and automobile components, and are particularly suitable for bonding optical materials, and can be suitably used for bonding and sealing components such as light bulbs, various types of lighting using LEDs, indicator lights, and displays. Furthermore, a laminate including an adhesive layer made of the adhesive of the present invention is suitably used for a flexible flat cable. EXAMPLES
[0044] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0045] 1. Evaluation method (1) Polyester resin composition 1H-NMR measurement was performed using an NMR measurement device (JNM-LA400 manufactured by JEOL Ltd.), and the resin composition was determined from the integrated intensity of the peaks of the copolymerization components in the obtained chart. Note that deuterated chloroform was used as the measurement solvent.
[0046] (2) Glass transition temperature of polyester resin Measurements were performed using an input compensation type differential scanning calorimeter (PerkinElmer, Diamond DSC, detection range: -50°C to 200°C) at a heating rate of 10°C / min. The glass transition temperature was determined as the temperature at the intersection of a straight line extending the low-temperature side baseline to the high-temperature side in the obtained heating curve and a tangent drawn at the point where the gradient of the curve in the stepwise change portion of the glass transition was maximum.
[0047] (3) Number average molecular weight of polyester resin The number average molecular weight in terms of polystyrene was measured by gel permeation chromatography (GPC) under the following conditions. [Liquid delivery unit]: Shimadzu LC-10ADvp [UV-Visible spectrophotometer]: Shimadzu SPD-6AV, detection wavelength: 254 nm [Column]: One Shodex KF-803 and two Shodex KF-804 columns connected in series [Solvent]: Tetrahydrofuran [Measurement temperature]: 40℃
[0048] (4) Adhesion (initial adhesion) The adhesives obtained in the examples and comparative examples were applied to a PET film (manufactured by Unitika Ltd., thickness 50 μm). Using a tabletop coating device (Yasuda Seiki Co., Ltd., film applicator No. 542-AB type, bar coater attached), adhesive was coated on the PET film so that the film thickness after drying would be 30 μm, and the film was dried in a hot air dryer at 100 ° C for 30 seconds, and aged at 50 ° C for 96 hours to produce a laminate 1 in which an adhesive layer was formed on the PET film. Next, a copper foil (Hitachi Metals Neomaterial Co., Ltd., thickness 30 μm) was superimposed on the adhesive layer surface of the laminate 1, and a small heat press machine (Hayashi Machinery Manufacturing Co., Ltd. SG-1300) was used to heat-press the laminate 2 for 30 seconds under conditions of a temperature of 180 ° C and a pressure of 0.2 MPa. The laminate 2 obtained was cut into a rectangular shape of 250 mm long x 25 mm wide to prepare a test piece. This test piece was subjected to a T-peel test under conditions of a temperature of 23 ° C and a tensile speed of 50 mm / min using a small tabletop tensile tester (Shimadzu Corporation EZ-SX). The adhesive strength was evaluated according to the following criteria. ◎:30N / 25mm or more ○: 20N / 25mm or more, less than 30N / 25mm △: 15N / 25mm or more, less than 20N / 25mm ×: Less than 15N / 25mm
[0049] (5) Heat and cold resistance The adhesive strength obtained in (4) was defined as the initial adhesive strength. A thermal shock test was also conducted on the test pieces prepared under the same conditions as in (4). The thermal shock test consisted of holding at -40°C for 30 minutes, then heating to 120°C and holding there for 30 minutes, with this cycle being repeated 1000 times in total. Thereafter, the adhesive strength was measured under the same conditions as in (4), and the adhesive strength obtained was defined as the adhesive strength after the thermal shock test. The retention rate was calculated using the following formula, and was evaluated according to the following criteria. Retention rate (%) = Adhesion strength after thermal shock test / Initial adhesive strength x 100 ◎: Retention rate is 90% or more ○: Retention rate is 80% or more, but less than 90% △: Retention rate is 70% or more but less than 80% ×: Retention rate is less than 70%
[0050] (5) Moisture and heat resistance The adhesive strength obtained in (4) was defined as the initial adhesive strength. In addition, for test pieces prepared under the same conditions as in (4), a moist heat test was carried out for 1000 hours under conditions of 85°C x 85% RH, and then the adhesive strength was measured under the same conditions as in (4), and the adhesive strength obtained was defined as the adhesive strength after the moist heat test. The retention rate was calculated using the following formula and evaluated according to the following criteria. Retention rate (%) = Adhesive strength after heat and humidity test / Initial adhesive strength x 100 ◎: Retention rate is 90% or more ○: Retention rate is 80% or more, but less than 90% △: Retention rate is 70% or more but less than 80% ×: Retention rate is less than 70%
[0051] (6) Blocking resistance The adhesive layer-formed surface of the laminate 1 obtained in (4) was overlapped with a PET film (manufactured by Unitika Ltd., thickness 50 μm), and the laminate was heated at 2 kg / cm 2 After applying a load of 1000 mm and maintaining the sample at 40° C. for 24 hours, the PET film was peeled off and the condition was evaluated according to the following criteria. 〇: PET film can be peeled off without resistance △: There is slight resistance when peeling off the PET film. ×: There is a large resistance when peeling off the PET film.
[0052] 2.Raw materials (1) The following materials were used as raw materials for the polyester resin: TPA: Terephthalic acid IPA: Isophthalic acid SDA: Sebacic acid EG: Ethylene glycol NPG: Neopentyl glycol PTMG1000: Polytetramethylene ether glycol (number average molecular weight: 1000) PEG1000: Polyethylene glycol (number average molecular weight: 1000)
[0053] (2) Preparation of polyester resin Polyester resin (A) 32g (50 mol%) of terephthalic acid, 32g (50 mol%) of isophthalic acid, 17g (70 mol%) of ethylene glycol, 24g (60 mol%) of neopentyl glycol, and 19g (5 mol%) of polytetramethylene glycol having a number average molecular weight of 1000 were charged into a reactor, and the inside of the system was replaced with nitrogen. Then, while stirring these raw materials at 1000 rpm, the reactor was heated to 240°C and melted. After the temperature inside the reactor reached 240°C, the esterification reaction was allowed to proceed for 4 hours. After 4 hours had passed, 0.2g of tetrabutyl titanate was added as a polymerization catalyst, and the inside of the system was decompressed. After the inside of the system reached a high vacuum (pressure: 20 Pa), the polymerization reaction was allowed to proceed for another 4 hours to obtain a copolymer polyester resin (A). The results of the copolymer composition of the polyester resin are shown in Table 1.
[0054] [Table 1]
[0055] Polyester resin (B~K) Except for changing the types and amounts of monomers used as shown in Table 1, polyester resins (B to K) having the copolymerization compositions shown in Table 1 were prepared in the same manner as polyester resin (A).
[0056] (3) Polyisocyanate X1: Isocyanurate of pentamethylene diisocyanate (Mitsui Chemicals, STABIO D-370N) X2: Isocyanurate of tolylene diisocyanate (Mitsui Chemicals, Takenate D-204EA-1) X3: Isocyanurate of hexamethylene diisocyanate (Asahi Kasei Corporation, TPA-100) X4: Isocyanurate-allophanate of pentamethylene diisocyanate (Mitsui Chemicals, STABIO D-376N) X5: Pentamethylene diisocyanate (Mitsui Chemicals, Stabio PDI)
[0057] Example 1 Polyester resin (A) was dissolved in methyl ethyl ketone to a solids concentration of 25%, and bis(pentabromophenyl)ethane (SAYTEX8010, manufactured by Albemarle Corporation) as a flame retardant, and antimony trioxide, titanium oxide, and silica (Aerosil R972, manufactured by Nippon Aerosil Co., Ltd.) as flame retardant assistants were added to the polyester resin solution in a mass ratio (polyester resin / bis(pentabromophenyl)ethane / antimony trioxide / titanium oxide / silica) of 50 / 25 / 17 / 5 / 3, and the mixture was dispersed for 2 hours using glass beads and a paint shaker (manufactured by Seiwa Giken Co., Ltd.). Further, polyisocyanate (Stabio D-370N manufactured by Mitsui Chemicals) was added so that the equivalent ratio (NCO / OH) of isocyanate groups to hydroxyl groups of the polyester resin was 2 equivalents to obtain an adhesive. Various evaluations were carried out using the obtained adhesive. The results are shown in Table 2.
[0058] Examples 2 to 14, Comparative Examples 1 to 6 Various evaluations were carried out in the same manner as in Example 1, except that the type of polyester resin, the type of polyisocyanate, and the equivalent ratio were changed as shown in Table 2. In Example 14, an adhesive was prepared in the same manner as in Example 1, except that no flame retardant or flame retardant assistant was added. The results are shown in Table 2.
[0059] [Table 2]
[0060] The resin compositions of the present invention in Examples 1 to 14 had excellent initial adhesiveness, and also had high adhesive strength retention after dry heat treatment and wet heat treatment, and were therefore excellent in durability.
[0061] In Comparative Example 1, the amount of aromatic carboxylic acid in the polyvalent carboxylic acid component was less than 80 mol %, and therefore the cold-heat resistance and moist heat resistance were poor. Comparative Example 2, which did not contain polyalkylene glycol in the polyol component, was poor in all of the initial adhesion, cold and heat resistance, and moist heat resistance. In Comparative Example 3, the content of polyalkylene glycol in the polyol component was less than 1 mol %, and therefore the initial adhesiveness and moist heat resistance were poor. In Comparative Example 4, an aromatic isocyanate derivative was used as the polyisocyanate, and therefore the initial adhesion was poor. Comparative Example 5 was poor in cold and heat resistance and moist heat resistance because a hexamethylene diisocyanate derivative was used as the polyisocyanate. In Comparative Example 6, since pentamethylene diisocyanate was used as the polyisocyanate, the adhesiveness, cold and heat resistance, and moist heat resistance were poor.
Claims
1. A resin composition containing a polyester resin and a polyisocyanate, wherein the polyester resin is composed of a polycarboxylic acid component containing an aromatic carboxylic acid at a ratio of 80 mol % or more in 100 mol % of an acid component, and a glycol component containing a polyalkylene glycol at a ratio of 1 mol % or more in 100 mol % of a glycol component, and the polyisocyanate is a pentamethylene diisocyanate derivative.
2. 2. The polyester resin composition according to claim 1, wherein the equivalent ratio (NCO / OH) of isocyanate groups to hydroxyl groups of the polyester resin is 0.5 to 5.
0.
3. 3. The polyester resin composition according to claim 1, wherein the number average molecular weight of the polyester resin is from 10,000 to 35,000.
4. 3. The polyester resin composition according to claim 1, wherein the polyalkylene glycol is polytetramethylene ether glycol.
5. An adhesive comprising the polyester resin composition according to claim 1 or 2.
6. A laminate comprising an adhesive layer made of the adhesive according to claim 5.
7. A flexible flat cable comprising the laminate according to claim 6.
Citation Information
Patent Citations
Coating composition, laminate and flexible flat cable
JP2008150443A